Successive duopoly under moral hazard: Will incentive contracts persist? - Marta Fernández Olmos; Jorge Rosell Martínez; Manuel Antonio Espitia-Escuer; Luz Maria Marin Vinuesa (Journal of Industrial Engineering and Management (JIEM), 2009)
The central purpose of this paper is to examine the incentive contract as an equilibrium phenomenon. We analyse a model of vertical differentiation in which we deal with the strategic role of the competitor's decisions in a successive duopoly. Is it better for a processor to offer an incentive contract to an upstream producer or the spot market? We determine the equilibrium of a game in which the processors simultaneously decide whether to offer an incentive contract or to continue at the spot market to acquire their input. Our results show that under successive duopoly, offering an incentive contract constitutes the unique equilibrium solution, which highlights the incentive contract persistence.
Keywords: 650; incentive contract; moral hazard; successive duopoly; equilibrium